Ang apat na sukat sa pagbasa at ang kaugnayan nito sa pagtuturo ng panitikan sa ikalima at ikaanim na baitang ng mababang paaralan sa kapaligirang pang-unang wika - Orillos, Lorenzo Q. 1947- (s.n.], 1973)
The modern trend in teaching a literary piece in the intermediate grade is to use the approach known as the four dimensions in reading, with understanding as the primary skill being developed. This strategy and its effects in teaching literature to fifth and sixth grade students with Filipino as their first language was presented in this paper using the following methods of study: personal interview, questionnaire, direct observation, documentary analysis and demonstration teaching.